2015
DOI: 10.1016/j.molonc.2015.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Nrf2 in healthy and malignant ovarian epithelial cells: Protection versus promotion

Abstract: Oxidative stress Nrf2 (NFE2L2) BRCA1 PARP inhibitor A B S T R A C TRisk factors indicate the importance of oxidative stress during ovarian carcinogenesis. To tolerate oxidative stress, cells activate the transcription factor Nrf2 (Nfe2l2), the master regulator of antioxidant and cytoprotective genes. Indeed, for most cancers, hyperactivity of Nrf2 is observed, and siRNA studies assigned Nrf2 as therapeutic target. However, the cancer-protective role of Nrf2 in healthy cells highlights the requirement for an ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 66 publications
0
16
0
Order By: Relevance
“…As previously described 59 , sensitivity toward ROS-induced cell death was determined using propidium iodide (PI) as marker for late apoptotic/necrotic cells. Cells were stained for 10 min with 5 μg/mL PI (Sigma-Aldrich) in PBS at 4 °C in the dark.…”
Section: Methodsmentioning
confidence: 99%
“…As previously described 59 , sensitivity toward ROS-induced cell death was determined using propidium iodide (PI) as marker for late apoptotic/necrotic cells. Cells were stained for 10 min with 5 μg/mL PI (Sigma-Aldrich) in PBS at 4 °C in the dark.…”
Section: Methodsmentioning
confidence: 99%
“…KEAP1 fosters IKKβ ubiquitination and autophagic degradation, thus allowing the downregulation of NF-κΒ signaling 53,71 . Accordingly, with the cytoprotective role of Nrf2 in tumor cells 72,73 , Lee and colleagues demonstrated that proteasome inhibitors favored IκBα degradation by triggering Nrf2-mediated autophagy.…”
Section: Nf-κb Regulates Autophagy In Cancer Cellsmentioning
confidence: 99%
“…Thioredoxin is involved in redox regulation of transcription factors such as NF-κB, NRF2, forkhead box class O (FOXO) proteins, reducing factor-1 (ref-1), and hypoxia inducible factor (HIF-1α), thereby increasing their binding to the DNA. Most of these transcription factors promote tumor growth and progression by regulating expression of genes that affect cell survival and growth [ 83 , 84 ]. For example, FOXO, NRF2, and ref-1 transcription factors upregulate transcription of anti-oxidant proteins that scavenge free radicals and allow survival of damaged or transformed cells [ 85 ].…”
Section: Inflammation and Eoc Initiation And Progressionmentioning
confidence: 99%